“Non-campaign of a non-candidate” - Alexei Navalny in the 2018 presidential election in Russia - Donaj, Łukasz; Kusa, Natalia (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2018)
In March 2018, another presidential election took place in the Russian Federation. For the fourth time Vladimir Putin won the election by a large majority of votes. Alexei Navalny - an opposition candidate who had been preparing his election campaign since the end of 2016 - was not allowed to stand in the election. Regardless of his elimination from the election, Navalny remained an active member of Russian political life before and after the election; he carried out a boycott of the election, and organized post-election protests. Without a doubt, despite the ban on running in the election, Navalny was one of the main figures in the electoral process. Thus, the aim of this article is a detailed analysis of Navalny’s preparations for the campaign - the authors focused not only on the candidate’s opposition activity, but also on his unique measures and methods of running a campaign (Internet, social media, crowdfunding). The article examines the campaign preparations, as well as the reasons for the rejection of Navalny’s registration as an election candidate, social support index, relationships with other candidates and the change of strategy after the Central Election Commission’s decision. The analysis is based on Russian law, Central Election Commission’s decisions, opinion poll results and information from the Russian and international media.

W marcu 2018 r. w Federacji Rosyjskiej odbyły się kolejne wybory prezydenckie. Elekcję po raz czwarty, zdecydowaną większością głosów, wygrał Władimir Putin. Do udziału w rywalizacji na urząd prezydenta nie został dopuszczony Aleksiej Na¬walny - opozycjonista, który swoją kampanię wyborczą przygotowywał od końca 2016 r. Pomimo eliminacji z procesu wyborczego, A. Nawalny pozostał aktywnym uczestnikiem życia politycznego Rosji przed i po wyborach, przeprowadził także akcję bojkotu wyborów oraz zorganizował powyborcze protesty. Nie ulega wątpliwości, iż pomimo zakazu udziału w elekcji, A. Nawalny był jedną z kluczowych postaci procesu wyborczego. Dlatego też, celem artykułu jest pogłębiona analiza przygotowań do kampanii A. Nawalnego - autorzy skupili się nie tylko na opozycyjnej działalności kandydata, ale również na unikalnych środkach i metodach prowadzenia przez niego kampanii (internet, media społecznościowe, crowdfunding). W ramach artykułu omówione zostały nie tylko przygotowania do kampanii, ale również przyczyny odmowy rejestracji A. Nawalnego jako kandydata, wskaźniki społecznego poparcia, relacje z innymi kandydatami oraz zmiana strategii po decyzji komisji wyborczej. Analiza powstała w oparciu o badania nad aktami rosyjskiego prawa, decyzjami centralnej komisji wyborczej, wynikami badań opinii publicznej oraz przekazami w rosyjskich i międzynarodowych mediach
„Nie/kampania nie/istniejącego kandydata” -Aleksiej Nawalny w wyborach prezydenckich w Rosji w 2018 r.
Keywords: Russian elections; Russian president; Alexei Navalny; election campaign; political opposition; wybory w Rosji; Prezydent Rosji; A. Nawalny; kampania wyborcza; opozycja polityczna